Achieving both low thermal expansion and low birefringence for polyimides by regulating chain structures. (8th May 2023) - Sun, Qiangsheng; Feng, Yudi; Guo, Jia; Wang, Changchun
Graphical abstract: Highlights: High-performance poly(amide imide)s possess low coefficient of thermal expansion. The DBCOD-containing poly(amide imide)s can undergo conformation transition. The conformation transition can be regulated by the chain structures of poly(amide imide)s. The polymer of PAI- c -P achieves both low thermal expansion and low birefringence. Abstract: The synthesis of polyimides (PIs) with both low coefficient of thermal expansion (CTE) and low birefringence still faces a big challenge. In this study, we prepared a new kind of PI (PI- c -P), derived from a diamine monomer ( cis -diamine-DBCOD) that contains dibenzocyclooctadiene (DBCOD) units, which exhibits near-zero thermal expansion with a CTE value of 1.5 ppm/K in the temperature range of 0–150 °C due to the unique conformation transition of DBCOD unit. The increase in chain rigidity and cis -diamine-DBCOD content could effectively reduce the CTE values by promoting conformation transition. Cross-linking could restrict chain conformation transition and impair thermal contraction, leading to higher CTE values. Unlike the conventional low CTE PIs with high orientation or crystallization, the birefringence of DBCOD-containing PI films was in the range of 0.0021 ∼ 0.0094, showing both low birefringence and low thermal expansion, this property is extremely important for its application in optical and electronic devices.